A multiple-image encryption algorithm based on orthogonal arrays with strength 3 - Xu, Ming (Optics and laser technology, 2023)
•Orthogonal array with strength 3 has few applications in cryptography to date, although it possesses some excellent cryptographic properties. This paper tries an image encryption algorithm based on this configuration. Simulation results demonstrate the proposed algorithm has good statistical characteristics and strong diffusivity.•The algorithm can encrypt multiple images simultaneously. The cipher images in the same batch are highly correlated, which makes the attacks more difficult. Moreover, if one cipher image is lost, its partial information can be recovered by other cipher images in the same batch.•Unlike other algorithms based on combinatorial configurations, the proposed algorithm doesn’t generate the whole configuration. It generates the designated element in orthogonal arrays only when needed. This strategy is more time-saving, and makes the algorithm not limited by the size of encrypted images. In recent years, remote working and studying lead to numerous images being transmitted on the Internet. Many of these images need protection from illegal obtaining or malicious peeping. Under the circumstances, the demand for image encryption algorithms with sufficient capacity and high efficiency is increasing. Multiple-image encryption algorithms can suit the demand well. This paper proposes a multiple-image encryption algorithm based on orthogonal arrays with strength 3. Orthogonal array is a typical configuration in combinatorial design theory, but the application research of orthogonal arrays with strength 3 in image encryption is still a blank. The proposed algorithm combines orthogonal arrays and chaotic maps perfectly to generate multiple 3D permutation maps and substitution maps, then multiple images can be encrypted efficiently. In simulation experiments, the average value of information entropy is 7.9993, the average value of PSNR is 8.884, the average value of MSD is 50, the average values of NPCR and UACI are 99.6127% and 33.4765% respectively. The numerical results demonstrate that the algorithm has enough ability to resist common attacks.